Profile of invasive group A and group B streptococcal infections in patients hospitalized at the University Hospital for Infectious Diseases "Dr. Fran Mihaljević" during the period from 2011 to 2018 : Profil invazivnih infekcija izazvanih invazivnim sojevima streptokoka grupe A i B kod pacijenata hospitaliziranih u Klinici za infektivne bolesti "Dr. Fran Mihaljević" u razdoblju od 2011. do 2018. godine - Šepec Rožmarić, Lana (Array, 2020)
Aim: Beta-haemolytic streptococci (BHS) rarely cause invasive disease (ID). Usually the most common cause of ID is group B BHS (BHS-B). However, in our recent routine work higher number of group A BHS (BHS-A) isolates from blood was noted. The aim of this study was to report trends and findings by group BHS-A and BHS-B causing laboratory confirmed disease from 2011 to 2018 at the University Hospital for Infectious Diseases „Dr. Fran Mihaljević”. Methods: Data on patients from the electronic database of microbiological laboratory at UHID for the period 2011-2018 was collected and analysed. Results: During the period 2011-2018, 151 BHS A and B were identified from normally sterile body sites. Most isolates were from blood cultures (96.7%). BHS-A and BHS-B were isolated almost equally. The highest number of isolates was recorded in 2012 and 2017. The number of BHS A isolates peaked in 2012, 54% more than BHS-B, and 50% more in 2016. Children presented 19.9% of patients, and were mostly isolated with BHS-A. 80.1% patients were adults. Adults predominated in the age group >65 years. 12 children and 18 adults were hospitalised in intensive care unit. Conclusion: Invasive group A and group B streptococcal infections predominantly affect most vulnerable age groups, children and elderly. In this study invasive BHS disease is most common among adults above 65 years of age. BHS-A was most common cause of invasive disease among paediatric patients as well as in the age group above 65 years. Typing and characterization of BHS-A isolates due to its characteristics should be foreseen as important diagnostic tool, especially to monitor changes in virulence and to prevent potential outbreaks.